Dose–response relationship between thyroid stimulating hormone and hypertension risk in euthyroid individuals. Issue 1 (January 2019) - He, Weiwei; Li, Sheli; Wang, Bin; Mu, Kaida; Shao, Xiaoqing; Yao, Qiuming; Li, Ling; Li, Qian; Zhang, Jin-an
Abstract : Background: The adverse impact of thyroid dysfunction on cardiovascular system is well established, but the relationship between the level of thyroid stimulating hormone (TSH) and the risk of hypertension in euthyroid individuals is still inconclusive. Methods: We carried out a population-based, cross-sectional study to evaluate the relationship between TSH and hypertension risk in euthyroid individuals, and logistic regression analysis was utilized. In addition, a dose–response meta-analysis of relevant cohort or cross-sectional studies was carried out to further assess the impact of TSH on hypertension risk among euthyroid individuals. Results: A total of 2289 euthyroid individuals without thyroid diseases were recruited in our cross-sectional study. Serum TSH level within the upper reference range was associated with higher risk of hypertension [odds ratio (OR) = 1.29, 95% confidence interval (CI) 1.04–1.61, P  = 0.023], and the OR for hypertension was still statistically significant after adjustment for confounding factors (OR = 1.32, 95% CI 1.01–1.72, P  = 0.041). Moreover, meta-analysis suggested an obvious dose–response relationship between TSH and hypertension risk in euthyroid individuals, and the OR for hypertension associated with per 1 mIU/l increase in TSH level was 1.09 (95% CI 1.04–1.14, P  < 0.001). Meta-analysis also showed that the β-coefficients of SBP and DBP associated with per 1 mIU/l increase in TSH level were 0.78 (95% CI 0.37–1.18, P  < 0.001) and 0.45 (95% CI 0.15–0.76, P  = 0.004), respectively. Conclusion: The current study provides strong evidence for the dose–response relationship between serum TSH level and hypertension risk in euthyroid individuals. Euthyroid individuals with higher normal TSH level are at higher risk of developing hypertension than those with lower normal TSH level. Abstract : Supplemental Digital Content is available in the text